Integrative pediatrics - Culbert, Timothy; Olness, Karen (Weil integrative medicine library., 2010)
There is ample evidence that children and adolescents in large numbers are actively using integrative (complementary and alternative) therapies. Various studies now indicate that over 50% of pediatricians surveyed would refer a patient for integrative therapy, and they would welcome more natural therapies for children provided they were safe and effective. However, there has been little training for pediatricians in this area. Integrative Pediatrics addresses these issues and provides guidelines for pediatricians, parents, and general audiences in a balanced, evidence-based manner. In this vol.